The clinical and epidemiological features of HHV-6A and HHV-6B infections in children of Moscow - M. Yu. Lysenkova; E. V. Melekhina; N. V. Karazhas; O. A. Svitich; P. A. Veselovsky; T. N. Rybalkina; R. E. Boshyan; V. V. Kosenchuk; A. D. Muzyka; A. V. Gorelov; D. V. Usenko; M. Yu. Ivanova (Детские инфекции (Москва), 2019)
Human herpes virus type 6 (HHV-6) is the etiological agent of plenty diseases. The form of the developing pathology depends on the localization of the virus in T-lymphocytes and on virus type: HHV-6A or HHV-6B, but identification of the type is possible by nucleotide sequence only. In Russia, researching on the typing of HHV-6 are conducted in Moscow and St. Petersburg mainly, but results is discordant. Also the prevalence of HHV-6A and HHV-6B among various population groups is of particular interest.